The Islamic approach to conserving biodiversity for global sustainability: an exploration - Laxman, Lekha; Ansari, Abdul Haseeb; Zawawi, Majdah (AENSI Publications, 2014)
Cultural and biological diversity is closely interwoven to form a symbiotic relationship which may in fact hold the key to global sustainability. Some of the major religions of the world contain the blueprints for the conservation of natural biodiversity since it provides the ethical and social models for regulating our relationship with nature. Islam provides a holistic approach in addressing the current global crisis in the face of loss of biodiversity for itpropagates balancing conservation with sustainable use of nature and the wealth of resources found therein. This article explores the fundamental principles enshrined in Islam and discusses their relevance in addressing the extinction crisis which is threatening the future of this planet as has been prophesized in the Qur‟an. The findings are based on a qualitative research design which employs a contents analysis of translations of Qur‟an and related studies that discusses the provisions therein. Islamic perspectives on crucial areas that impact on biodiversity such as sustainable development, fair trade, the sustainable utilization of biodiversity through biotechnology and related issues such as biosafety, benefit sharing and intellectual property rights were discussed.The article concludes thatit is timely to re-explore and tap the potential of religious values to shape the way people think and behave as well as the way they relate to the natural world in the face of environmental crisis faced by the global population. Conservation efforts undertaken through holistic approaches prescribed by holistic principles enshrined in Islam may be the requisite tool that is needed to unite the global community and find pathways to live harmoniously with the environment.